A inserção da variável climática no licenciamento ambiental como ferramenta de mitigação das mudanças climáticas - Moura, Giovanna Paola Batista de Britto Lyra (2023)
Currently, the world faces serious problems arising from the action of man in the face of nature and natural resources, whose unbridled exploitation generated, among other environmental changes, a significant increase in the occurrence of climate change, mainly caused by the emission of polluting gases in the earth’s atmosphere, as a potentializing factor of the greenhouse effect. Several international events were held to discuss not only the climate issue, but more specifically, ways of reducing greenhouse gas (GHG) emissions into the atmosphere, with emphasis, among others, for the 21st Conference of the Parties of the United Nations Framework Convention on Climate Change, which resulted in the drafting of the Paris Agreement, adopted on 12 December 2015. The signatories of this treaty have the obligation to develop and implement internal instruments to combat and adapt to climate change, with a view to meeting the gas emission reduction targets assumed by its agreement, from the development of an environmental policy based on climate concern. In Brazil, one of the most valuable environmental policy instruments is environmental assessment, which is an administrative procedure that aims to exercise preventive control and monitoring of activities that use natural resources and that are potentially causing environmental impact. Despite its importance as an instrument of national environmental policy, initiatives to insert the climate variable in the administrative procedures for granting and renewing environmental assessment for potentially polluting activities in Brazil are still incipient. In this sense, the present study aims to analyze the normative and methodological feasibility of the insertion of the climate variable in the processes of granting and renewing environmental assessment in the country in this country. To answer the research question, it is used the qualitative approach, with the bibliographic and documentary data collection techniques, as well as the use of the comparative method, performed through the functionalist method, involving the comparison of Brazilian legislation with international legislation on environmental licensing.